INSPIRE: INvestigating Stellar Population In RElics: VII. The local environment of ultra-compact massive galaxies - Scognamiglio, Diana; Spiniello, Chiara; Radovich, Mario; Tortora, Crescenzo; Napolitano, Nicola R; Li, Rui; Maturi, Matteo; Maksymowicz-Maciata, Michalina; Cappellari, Michele; Arnaboldi, Magda; Bevacqua, Davide; Coccato, Lodovico; et al. (Monthly notices of the Royal Astronomical Society, 2024)
Relic galaxies, the oldest ultra-compact massive galaxies (UCMGs), contain almost exclusively ‘pristine’ stars formed during an intense star formation (SF) burst at high redshift. As such, they allow us to study in detail the early mechanism of galaxy assembly in the Universe. Using the largest catalogue of spectroscopically confirmed UCMGs for which a degree of relicness (DoR) had been estimated, the INSPIRE catalogue, we investigate whether or not relics prefer dense environments. The objective of this study is to determine if the DoR, which measures how extreme the SF history was, and the surrounding environment are correlated. In order to achieve this goal, we employ the AMICO galaxy cluster catalogue to compute the probability for a galaxy to be a member of a cluster, and measure the local density around each UCMG using machine learning-based photometric redshifts. We find that UCMGs can reside both in clusters and in the field, but objects with very low DoR ($\lt 0.3$, i.e. a relatively extended SF history) prefer underdense environments. We additionally report a correlation between the DoR and the distance from the cluster centre: more extreme relics, when located in clusters, tend to occupy the more central regions of them. We finally outline potential evolution scenarios for UCMGs at different DoR to reconcile their presence in both clusters and field environments.